2005
DOI: 10.1111/j.1528-1167.2005.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset and Slow‐progressing Lafora Disease in Four Siblings with EPM2B Mutation

Abstract: Summary:We report a family with four brothers affected by Lafora disease (LD). Mean age at onset was 19.5 years (range, 17-21). In all cases, the initial obvious symptoms were diffuse myoclonus and occasional generalized tonic-clonic seizures (GTCSs), followed by cognitive difficulties. Severity of myoclonus, seizure diaries, and neurologic and neuropsychological status were finally evaluated in March 2005. The duration of follow-up was >10 years for three subjects. Daily living activities and social interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 7 publications
2
59
1
2
Order By: Relevance
“…Because exon 1 of the EPM2A gene encodes the carbohydrate-binding domain, a role for this domain in the childhood onset symptoms was suspected [Ganesh et al, 2002b]. Although no such report exists for the subdomains of NHLRC1 gene, independent reports have demonstrated that LD patients with NHLRC1 mutations tend to live longer than those with EPM2A mutations [Baykan et al, 2005;Franceschetti et al, 2006;GomezAbad et al, 2005;Singh et al, 2006]. Based on these findings, Singh et al (2006) proposed that not all functions of laforin could be regulated by malin.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because exon 1 of the EPM2A gene encodes the carbohydrate-binding domain, a role for this domain in the childhood onset symptoms was suspected [Ganesh et al, 2002b]. Although no such report exists for the subdomains of NHLRC1 gene, independent reports have demonstrated that LD patients with NHLRC1 mutations tend to live longer than those with EPM2A mutations [Baykan et al, 2005;Franceschetti et al, 2006;GomezAbad et al, 2005;Singh et al, 2006]. Based on these findings, Singh et al (2006) proposed that not all functions of laforin could be regulated by malin.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…The figure also shows (bottom) the genomic organization of the NHLRC1 gene and locations of the large deletions associated with LD. Mutations were tabulated from the following PubMed-indexed English articles reporting the mutations [Baykan et al, 2005;Chan et al, 2003;Franceschetti et al, 2006;Gomez-Abad et al, 2005;Ianzano et al, 2004;Lohi et al, 2007;Singh et al, 2005Singh et al, , 2006Singh et al, , 2008Striano et al, 2008;Turbull et al, 2008]. Mutation numbering is based on GenBank reference protein sequence with accession number NP_940988.2.…”
Section: Clinical and Diagnostic Relevancementioning
confidence: 99%
“…Mild brain atrophy has been described in 35–40% of patients with typical and mild Lafora disease with normal MRI in the remaining patients 5, 14. The transient MRI abnormalities of our patient may well have been caused by the intensive seizure activity because they were localized in the area with the highest seizure activity registered on EEG and had normalized after 3‐month follow‐up.…”
Section: Discussionmentioning
confidence: 51%
“…Lafora hastalığı tipik olarak 12-15 yaşları arasında başlamakla beraber daha erken ve daha geç başlangıçlı varyantlar da bildirilmektedir. [1,2] …”
Section: Introductionunclassified